The Correlation Between Workload and Work Stress with Sleep Quality of Nurses at Husada Mulia Clinic, Lumajang - Amalia Firdaus Prasetyo; Alwin Widhiyanto; Nurul Laili (KHD Production, 2024)
The demands of work that want to be completed quickly result in a workload that has an impact on the physical and psychological. Excessive workload can cause work stress that has an impact on the provision of health services. Stress in nurses is generally caused by physical causes experienced during work and emotional fatigue, the emergence of work stress is also caused by excessive workload, so it can affect the quality of nurses' sleep. The purpose of this study was to analyze the relationship between workload and job stress with nurses' sleep quality at Husada Mulia Clinic, Lumajang. This study used a cross-sectional approach. The population and sample size were 40 respondents with a total sampling technique. Data processing includes editing, coding, scoring, tabulating, then analyzed with SPSS software using the chi-square test with α 0.05. The results of the chi-square test showed a relationship between workload and work stress with the sleep quality of nurses at the Husada Mulia Lumajang Clinic, with asymp values. Sig. (2-sided) = 0.043 and 0.017 ≤ α (0.05). The results showed that 23 respondents had a light workload, and 21 respondents had light work stress, while 29 respondents had good sleep quality. It is hoped that this study can provide knowledge and insight to nurses regarding workload and work stress with good sleep quality. And evaluate to be input to the management of the Husda Mulia Lumajang clinic to consider workload and work stress in nurses.